Association "neurotoxicity" of Toxic Metal Mercury in Hair with Autism Spectrum Disorders in Children - almayhi, Roaa; Kawass , Ghoufran (University of Thi-Qar Journal of Science, 2024)
Autism spectrum disorder is a complicated neurological disease that is identified by the occurrence of two defining characteristics present in people with ASD, notably social deficits and repetitive and stereotypical behaviors. This review aims to systematically investigate the relationship between the levels of toxic and trace element Hg in hair and the developments of ASD.. The objective of this review is to Methodically investigate the connection Amidst ASD" emergence, also" hair’ levels of hazardous, also trace elements Hg.. Through Original articles that reported on the amounts of trace elements Hair was incorporated. The majority of studies’ interests change grave not harmful state of being gathered or focused components "in the hair" of kids with neurodevelopmental disorders like ASD. A survey of field medicine describes demonstrated mercury exposure, whether organic, or inorganic can result in the development of characteristics symptoms that characterize or are frequently observed in autism spectrum disorders (ASD). The (DSM-IV) diagnostic criteria of autism include deficits with interpersonal relationships, having trouble expressing oneself, and engaging in behaviors that are both stereotypical and repetitious , all of which be brought on by mercury.